The Impact of Corporate ESG Performance on Institutional Investors’ Shareholding Ratio - Sun, Ruixi (International Journal of Global Economics and Management, 2024)
With the extensive dissemination and recognition of ESG investment concepts, ESG performance of enterprises has attracted widespread attention from all walks of life, and investors have gradually incorporated ESG performance into their investment decisions. The current study examines the impact of environmental, social and corporate governance (ESG) performance on institutional investors' shareholding. From 2012 to 2023, the data combined and analyzed by the data of the China A-SHARE market company. As a result of the study, companies with higher ESG scores tend to attract more attention and investment from institutional investors, which suggests that institutional investors are increasingly emphasizing corporate sustainability metrics in their asset allocation. Further research also found that internal control quality and information transparency play an important positive role in the relationship between the company's ESG performance and institutional investor shareholders.